A standardized production pipeline for high profile targets from Mycobacterium tuberculosis. Issue 9 (3rd August 2016) - Milewski, Morlin C.; Broger, Tobias; Kirkpatrick, Joanna; Filomena, Angela; Komadina, Dana; Schneiderhan‐Marra, Nicole; Wilmanns, Matthias; Parret, Annabel H. A.
Abstract : Purpose: Tuberculosis is still a major threat to global health. New tools and strategies to produce disease‐related proteins are quintessential for the development of novel vaccines and diagnostic markers. Experimental design: To obtain recombinant proteins from Mycobacterium tuberculosis (Mtb) for use in clinical applications, a standardized procedure was developed that includes subcloning, protein expression in Mycobacterium smegmatis and protein purification using chromatography. The potential for the different protein targets to serve as diagnostic markers for tuberculosis was established using multiplex immunoassays. Results: Twelve soluble proteins from Mtb, including one protein complex, were purified to near‐homogeneity following recombinant expression in M. smegmatis . Protein purity was assessed both by size exclusion chromatography and MS. Multiplex serological testing of the final protein preparations showed that all but one protein displayed a clear antibody response in serum samples from 278 tuberculosis patients. Conclusion and clinical relevance: The established workflow comprises a simple, cost‐effective, and scalable pipeline for production of soluble proteins from Mtb and can be used to prioritize immunogenic proteins suitable for use as diagnostic markers.